Answer:3/2
Step-by-step explanation:
3/2
Answer:
2(x + 1) = 10
x = 4
Step-by-step explanation:
Given:
2(x + 1) = 10
Solution:
Apply Distributive property
A*(B+C) = (A*B) + (A*C)
This means multiply 2 with x and 1
2*(x+1) = (2*x) + (2*1)
2x + 2 = 10
Use Subtraction property of equality
A = B, then A - C = B - C
Subtracting 2 from both sides:
2x + 2 - 2 = 10 - 2
2x = 8 Step 3
Use Division property of equality
It state that if you divide both sides of an equation by same nonzero number then the sides remain equal
Dividing both sides by 2
2x/2 = 8/2
x = 4
This means value of x is 4
Another method to solve this equation is:
2(x+1)=10
Use Distributive property
A*(B+C) = (A*B) + (A*C)
2*(x+1) = (2*x) + (2*1)
2*(x+1) = 2x + 2
Use commutative property
A + (-B) = (-B) + A
2x + 2 + (-2) = 2x + (-2) + 2
2x + 2 + (-2) = 10 + (-2)
2x + 2 - 2 = 10-2
2x = 8
Using division property
AX = B
AX / A = B / A
So
X = B/A
This becomes:
2x = 8
2x = 8.
Divide both sides by 2
2x / 2 = 8 / 2
x = 4
The solution to the system of equations x + 2y = 1 and -3x-2y = 5 is:
x = -3, y = 2
The given system of equations:
x + 2y = 1............(1)
-3x - 2y = 5..........(2)
This can be written in matrix form as shown:
![\left[\begin{array}{ccc}1&2\\-3&-2\end{array}\right] \left[\begin{array}{ccc}x\\y\end{array}\right] = \left[\begin{array}{ccc}1\\5\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%5C%5C-3%26-2%5Cend%7Barray%7D%5Cright%5D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7Dx%5C%5Cy%5Cend%7Barray%7D%5Cright%5D%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%5C%5C5%5Cend%7Barray%7D%5Cright%5D)
Find the determinant of ![\left[\begin{array}{ccc}1&2\\-3&-2\end{array}\right]](https://tex.z-dn.net/?f=%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%5C%5C-3%26-2%5Cend%7Barray%7D%5Cright%5D)

![\triangle_x = \left[\begin{array}{ccc}1&2\\5&-2\end{array}\right]\\\triangle_x = 1(-2)-2(5)\\\triangle_x = -2-10\\\triangle_x =-12](https://tex.z-dn.net/?f=%5Ctriangle_x%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%262%5C%5C5%26-2%5Cend%7Barray%7D%5Cright%5D%5C%5C%5Ctriangle_x%20%3D%201%28-2%29-2%285%29%5C%5C%5Ctriangle_x%20%3D%20-2-10%5C%5C%5Ctriangle_x%20%3D-12)
![\triangle_y = \left[\begin{array}{ccc}1&1\\-3&5\end{array}\right]\\\triangle_y = 1(5)-1(-3)\\\triangle_y = 5 + 3\\\triangle_y =8](https://tex.z-dn.net/?f=%5Ctriangle_y%20%3D%20%5Cleft%5B%5Cbegin%7Barray%7D%7Bccc%7D1%261%5C%5C-3%265%5Cend%7Barray%7D%5Cright%5D%5C%5C%5Ctriangle_y%20%3D%201%285%29-1%28-3%29%5C%5C%5Ctriangle_y%20%3D%205%20%2B%203%5C%5C%5Ctriangle_y%20%3D8)


The solution to the system of equations x + 2y = 1 and -3x-2y = 5 is:
x = -3, y = 2
Learn more here: brainly.com/question/4428059
Answer:
Acute triangle
Step-by-step explanation:
If you add up are those angle equations, set it equal to 0, 26x - 2 = 180, you get x = 7/ Plug that back into each equation, and you realize none of the angles are more than 90. This makes it an acute triangle.
Answer:
Yes
Step-by-step explanation:
They are similiar because the big triangle is a dialated version of the first one